Immigrants and the distribution of income and wealth in the euro area: First facts and implications for monetary policy - Maarten Dossche; Aleksandra Kolndrekaj; Maximilian Propst; Javier Ramos Perez; Jirka Slacalek (European Central Bank (ECB), 2022)
We use household surveys to describe differences in wages, income, wealth and liquid assets of households born in their country of residence ("natives") vs. those born in other EU and non- EU countries ("immigrants"). The differences in wealth are more substantial than the differences in wages and incomes: immigrants earn on average about 30% lower wages than natives and hold roughly 60% less net wealth. For all variables, only a small fraction of differences between natives and immigrants-around 30%-can be explained by differences in demographics (age, gender, marital status, education, occupation, sector of employment). Immigrants are more likely to be liquidity constrained: while about 17% of natives can be labelled as "hand-to-mouth" (holding liquid assets worth less than two weeks of income), the corresponding share is 20% for households born in another EU country and 29% for those born outside the EU. Employment rates of immigrants are substantially more sensitive to fluctuations in aggregate employment. Monetary policy easing stimulates more strongly employment of individuals born outside the EU.
Keywords: J15; D31; E52; 330; migration; inequality; monetary policy; distribution of income and wealth